Community Leaders’ Roles In Managing Security Challenges: Perspective of Community Dwellers in Rural Communities of Osun State, Nigeria : Community Leaders’ Roles In Managing Security Challenges - Famakinwa, Michael; Oyedokun, Margret Olayemi; Omiyinka, Samson Timilehin (Journal of Rural and Urban Community Studies, 2025)
This study investigated the roles of community leaders in managing security challenges in agrarian communities of Osun state, Nigeria. It identified prevailing security challenges and their causes; examined the perceived roles of community leaders in managing security challenges; and identified problems facing community leaders in tackling security challenges in their communities. The interview schedule was employed to gather information from 135 community members selected across the state through a multistage sampling procedure while 15 key informant interview sessions were conducted to collect qualitative data from 15 community leaders. Descriptive statistic was used to analyse quantitative data while content analysis was used to analyse qualitative data. The. Results showed that farmers-herders conflict (79.1%) and crop thefts and vandalism (45%) were the most prevailing and major causes of security challenges identified. While settlement of conflicts and disputes (90.4%), collaborating with law enforcement agents (87.1%) and creating awareness of security issues (80%) were the most prominent roles performed of community leaders in security management. Inadequate funds (80%) and poor communication and coordination (70.1%) were the major constraints facing community leaders in managing security challenges in rural communities. The study concluded the majority of the community members indicated that their leaders played a significant role in managing security challenges of their communities to ensure community peace and sustainable food security